PENGARUH METODE READING ALOUD TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN MAHASISWA JURUSAN BAHASA JEPANG - Liastuti Ustianingsih; Luluk Puji Riwayanti (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2016)
Reading comprehension is a process to recognize or identify text, and then recall the contents of the text. Reading comprehension can also be meant as an activity to make a sequence of descriptions, can be evaluated as well as to respond to what is expressed or implied in the text. Reading comprehension, especially in Japanese is required by students majoring in Japanese language in the course dokkai 2 (reading comprehension), due to a lack of proficiency in reading comprehension Japanese will make Japanese language is difficult, it is to help students understand the reading in Japanese, used active learning methods type of reading aloud. Active learning methods type of reading aloud can help improve students' understanding of the discourse, to remember vocabulary constantly, and recognize new words that appear in the context of the passage. The use of active learning methods type of reading aloud to facilitate the understanding of the Japanese language discourse. Because it was evident the students better understand Japanese discourse after use active learning methods type of reading aloud. In addition, the use of active learning methods type of reading aloud can create active learning and independent and attractive, so as to motivate the students to understand the discourse of Japanese.